OPTIMALISASI BAGI HASIL PADA PRODUK PEMBIAYAAN MUDHARABAH DALAM MENINGKATKAN LABA DAN MARKET SHARE - Nurrachmi, Layla; Zuraidah, Zuraidah (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2019)
Sharia in accounting are required to apply Sharia principles one is not allowed the existence of interest because it belongs in the category of usury, so that an Islamic banking system for the results, one of them on mudharabah financing, which is the core product of Sharia banking. The financial report on the statistics on Islamic banking income and market share of financing has the lowest proportion of mudharabah, optimization of products for mudharabah financing is important to increase Â profit and market share. This research is qualitative research by taking the location of research in PT Bank BRISyariah Malang Soekarno-Hatta. Data taken researchers use interview techniques and other secondary data, the researchers then perform data analysis and interpret the data obtained. The results of this research show that at PT Bank BRISyariah Malang branch Soekarno Hatta in applying the principle for the outcome has been in accordance with the rules of Fatwa DSN MUI No. 07/DSN-MUI/IV/2000, but Mudharabah financing is not a core product Because there are more uses for Mutanaqisah and Murabahah financing. The optimization efforts that have been done are not fully optimal, another way that can be done is to give fair incentives to customers who report their business honestly. If it can be applied then profit will increase so that the market share financing Mudarabah will also increase.